Utilizing Analytical Hierarchy Process for Evaluating the Performance of Straw Mushroom (Volvariella spp.) Farmers in North-Eastern Region of Karawang, West Java, Indonesia - Tuti Nur'aeni; Slamet Abadi; I Putu Eka Wijaya (Universitas Muhammadiyah Malang, 2024)
Producers of Straw Mushroom (Volvariella spp.) in the North-Eastern region of Karawang, West Java, Indonesia predominantly operate within the sub-districts of Cilamaya Kulon, Cilamaya Wetan, and Banyusari. A noticeable decline in Straw Mushroom cultivation has been observed in this region, which can be ascribed to various factors including suboptimal farming practices, diminished seed quality, and erratic weather conditions impacting production outcomes. It is imperative to enhance the efficiency of mushroom farming across multiple stages encompassing planning, procurement of raw materials, processing, Maintenance, harvesting, marketing, shipping, handling returns, and ensuring consumer satisfaction. This study aims to evaluate the productivity of mushroom farmers, with a specific focus on the top-performing farmers in the North-Eastern region of Karawang. Proportionate stratified random sampling was employed as the sampling technique, and data were collected through structured interviews utilizing a questionnaire. Quantitative analysis, employing the Analytical Hierarchy Process method, was utilized for data analysis. The findings reveal that planning criteria hold the highest priority value of 0.306, whereas satisfaction criteria have the lowest priority value of 0.018. The top-performing farmers achieved a score of 2.08, while the lowest performing farmers attained a score of 1.10